Establishing upper bounds in English monolingual and Heritage Spanish-English bilingual language development. (2nd January 2021) - Syrett, Kristen; Austin, Jennifer; Sanchez, Liliana
ABSTRACT: Quantificational elements such as some pose a challenge to young language learners, given their vague meaning and ability to take on an upper-bounded interpretation (relative to all ) in certain contexts. The challenge is enhanced when a child is acquiring multiple languages that do not share a one-to-one mapping between their lexical entries with some . Such is the case with some in English and unos and algunos in Spanish. Indeed, Heritage Spanish-English bilinguals have been documented as diverging from monolingual children and adults in their interpretation of algunos, which is said to lexically encode this upper-bounded meaning, although early Heritage bilinguals do not demonstrate this knowledge robustly. In this article, we ask how pervasive this challenge is by (a) investigating whether the same pattern holds in English, where there are not two words for some, and (b) comparing the pragmatic process for some to other linguistic items that either invoke another pragmatic process (particularized conversational implicature) or a semantic upper bound. Our results strongly suggest that the extended process of fine-tuning of quantificational lexical entries within and across languages precedes a pragmatic comparison of alternatives, but at the same time, Heritage bilinguals demonstrate pragmatic awareness beyond generalized conversational implicatures.